2019
DOI: 10.1002/ptr.6532
|View full text |Cite
|
Sign up to set email alerts
|

Aloe‐emodin: A review of its pharmacology, toxicity, and pharmacokinetics

Abstract: Aloe-emodin is a naturally anthraquinone derivative and an active ingredient of Chinese herbs, such as Cassia occidentalis, Rheum palmatum L., Aloe vera, and Polygonum multiflorum Thunb. Emerging evidence suggests that aloe-emodin exhibits many pharmacological effects, including anticancer, antivirus, anti-inflammatory, antibacterial, antiparasitic, neuroprotective, and hepatoprotective activities. These pharmacological properties lay the foundation for the treatment of various diseases, including influenza vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
108
0
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 338 publications
(122 citation statements)
references
References 86 publications
0
108
0
14
Order By: Relevance
“…In order to evaluate the quality and standard of preparations of BO, we detected and analyzed eight quality marker components in BO by HPLC, which contained aloe emodin, emodin, rhein, chrysophanol, ferulic acid, lobetyolin, asarinin, and borneol. The active compounds aloe emodin, emodin, rhein, and chrysophanol were reported to be quality markers of Rheum palmatum L. with antiinflammatory activity and to promote wound healing, and their pathways of action may be involved in the proliferation and differentiation of skin epithelial cells through the regulation of PI3K/AKT pathway (Dong et al, 2016;Wu et al, 2017;Dong et al, 2019;Su et al, 2020). Ferulic acid is a quality marker of Angelica sinensis (Oliv.)…”
Section: Discussionmentioning
confidence: 99%
“…In order to evaluate the quality and standard of preparations of BO, we detected and analyzed eight quality marker components in BO by HPLC, which contained aloe emodin, emodin, rhein, chrysophanol, ferulic acid, lobetyolin, asarinin, and borneol. The active compounds aloe emodin, emodin, rhein, and chrysophanol were reported to be quality markers of Rheum palmatum L. with antiinflammatory activity and to promote wound healing, and their pathways of action may be involved in the proliferation and differentiation of skin epithelial cells through the regulation of PI3K/AKT pathway (Dong et al, 2016;Wu et al, 2017;Dong et al, 2019;Su et al, 2020). Ferulic acid is a quality marker of Angelica sinensis (Oliv.)…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, they may probably be vital multifunctional active compounds of SXD against T2DM. It is well known that both quercetin [ 31 – 33 ] and aloe-emodin [ 34 ] exhibit a wide range of biological effects, including anti-inflammatory, antioxidant, anticancer, and especially the protective effect on T2DM. Youl et al [ 35 ] reported that quercetin could significantly increase insulin secretion via ERK1/2 phosphorylation in INS-1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…In the past few decades, many studies have reported that natural medicine has many advantages in the treatment of cancer [17][18][19]. Aloe-emodin is an anthraquinone compound widely found in plants such as Rheum palmatum L, Aloe, and has signi cant anti-in ammatory, analgesic, and anti-swelling effects [20]. Aloe-emodin has anti-cell proliferation and inducing apoptosis effects in many cancer cells [21,22]and aloe-emodin can cross HT-29 cellular membranes and pass through the intestinal layer [23].…”
Section: Discussionmentioning
confidence: 99%